WORKER'S HEALTH IN THE FAMILY HEALTH STRATEGY: THE NURSING TEAM'S PERCEPTIONS - Maria de Lourdes Custódio Duarte; Joice Carvalho Avelhaneda; Rodrigo Ritter Parcianello (Universidade Federal do Paraná, 2013)
The study aimed to analyze the nursing team's perceptions on the health of the Family Health Strategy worker in the South of Brazil. All the professionals from the nursing team were interviewed, totalling six workers. The data was analyzed following the steps of thematic analysis, and two categories emerged: Issues which affect the nursing team's health and Suggestions from the nursing team for improving the worker's health. The first category evidenced overloading with work, the physical structure, financial issues, security, and mental and physical suffering. The elements composing the second category are the creation of a place for relaxation and the setting-up of therapeutic groups, as well as the need for recognition of the work. It is concluded that workers' health must be grounded in meetings with managers, with a view to improving work conditions which influence the workers' health and, consequently, the quality of the care given to the population.